Vertical distribution of chlorophyllα in the Indian sector of the Antarctic Ocean in 1972-1973 - Kazunori Kuroda; Mitsuo Fukuchi (National Institute of Polar Research, 1982)
In the Indian sector of the Antarctic Ocean, vertical distribution of chlorophyll a down to a depth of 500m was investigated. The observations were carried out as part of the marine biological programs of the 14th Japanese Antarctic Research Expedition at six stations on the southward leg of the FUJI between 38°and 60°S along 105°E, two stations south of 60°S in December 1972,and at nine stations on the northward leg between 67°and 35°S along 15°E in February and March 1973. High surface chlorophyll a contents and the remarkable subsurface maximum of chlorophyll a were distributed in the Antarctic water on the southward leg. Integrated chlorophyll a stocks in a 0-250m water column were in the range of 17-129mg/m^2 and high values were found in the Antarctic water on the southward leg. The enhancement of chlorophyll a in late December seems to coincide with the blooming season of phytoplankton in the Antarctic water. The integrated stocks of chlorophyll a in the euphotic zone were in the range of 8-43mg/m^2. A large amount of chlorophyll a contents below the euphotic zone were distributed mainly in the Antarctic water. Positive correlations among surface chlorophyll a contents, subsurface chlorophyll a contents and integrated chlorophyll a stocks were found.